2015
DOI: 10.1016/j.gca.2015.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic carbon and nitrate loading on partitioning between dissimilatory nitrate reduction to ammonium (DNRA) and N2 production

Abstract: Biologically available nitrogen is removed from ecosystems through the microbial processes of anaerobic ammonium oxidation (anammox) or denitrification, while dissimilatory nitrate reduction to ammonium (DNRA) retains it. A mechanistic understanding of controls on partitioning among these pathways is currently lacking. The objective of this study was to conduct a manipulative experiment to determine the influence of organic carbon and nitrate loading on partitioning. Sediment was collected from a location on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(107 citation statements)
references
References 65 publications
(91 reference statements)
11
93
2
1
Order By: Relevance
“…For example, in a wastewater treatment system with high organic carbon and nitrate in the influent (as in aquaculture and industrial wastewater) or nitrate presence in a recirculation stream which is mixed with the influent, DNRA bacteria can be active. Co-occurrence of denitrification and DNRA in artificial wastewater treatment wetlands and natural ecosystems, such as sediments, is often reported in literature (Mørkved et al, 2005; Giblin et al, 2013; Hardison et al, 2015). To which extent the Ac/N ratio dependent co-occurrence of DNRA and denitrification is influenced by the nature of the electron donor/carbon source in the system (Giblin et al, 2013; Plummer et al, 2015) and the oxidized nitrogen compound utilized (i.e., nitrite or nitrate), will be the topic of future studies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, in a wastewater treatment system with high organic carbon and nitrate in the influent (as in aquaculture and industrial wastewater) or nitrate presence in a recirculation stream which is mixed with the influent, DNRA bacteria can be active. Co-occurrence of denitrification and DNRA in artificial wastewater treatment wetlands and natural ecosystems, such as sediments, is often reported in literature (Mørkved et al, 2005; Giblin et al, 2013; Hardison et al, 2015). To which extent the Ac/N ratio dependent co-occurrence of DNRA and denitrification is influenced by the nature of the electron donor/carbon source in the system (Giblin et al, 2013; Plummer et al, 2015) and the oxidized nitrogen compound utilized (i.e., nitrite or nitrate), will be the topic of future studies.…”
Section: Discussionmentioning
confidence: 92%
“…A low C/N ratio, i.e., low or limiting available organic carbon, has been suggested to promote denitrification. This effect of the C/N ratio has been widely observed in both aquatic and terrestrial ecosystems (Burgin and Hamilton, 2007; Rütting et al, 2011; Hardison et al, 2015), but this phenomenom has rarely been reproduced in controlled mixed culture systems in the laboratory.…”
Section: Introductionmentioning
confidence: 91%
“…2f). Regardless, the seasonally high organic matter deposition likely benefits denitrifiers over anammox bacteria in summer months since denitrification typically favours sites with higher OC delivery versus anammox, which tends to occur in organic-poor conditions84243. Anammox may be more prevalent down-slope or in the Arctic Ocean basin at deeper depths where organic matter delivery is more attenuated44 and where denitrification occurs at lower rates32, following the trend of ra observed in other shelf-slope transects14; however, further studies are required to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, only one-third of studies in temperate marsh and tropical mangrove systems report DNRA rates that exceed denitrification, which suggests other factors besides temperature have a role in its variability48. A high ratio of OC versus NO 3 − availability has been useful in predicting DNRA prevalence424348, but not without exceptions. DNRA dominated denitrification in hypoxic sediments in the Baltic Sea, where sediment organic matter was low compared with relatively high NO 3 − concentrations49.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported dissimilatory nitrate reduction in constructed wetlands [27][28]. Owing to the requirement for more electrons, dissimilatory nitrate reduction, which includes the reduction of NO 2 --N and NO 3 --N to NH 4 + -N, is considered favored by carbon-rich and nitrate-limited conditions [29]. In this study, the specific conditions of the BECW system at a lower temperature may promote the growth of nitrate-ammonifying bacteria and limit the activity of nitrite-reducing bacteria for such an unconventional transformation.…”
Section: Resultsmentioning
confidence: 99%